Исследование фазового состава, структуры и свойств многослойных вакуумно-дуговых нанокристаллических покрытий Ti-Mo-N - Андреев, А.А.; Соболь, О.В.; Горбань, В.Ф.; Столбовой, В.А.; Мамон, В.В. (Физическая инженерия поверхности, 2010)
Проведено дослідження впливу товщини шарів і умов одержання на фазовий склад, структуру і механічні характеристики (твердість і модуль пружності) вакуумно-дугових багатошарових наноструктурних покриттів Tі-Mo₂N. Показано, що при малій товщині шарів (≈2 нм) можливий эпітаксіальний ріст ізоструктурних кубічних модифікацій нітриду титану й нітриду молібдену без утворення двофазного стану. При більшій товщині відбувається формування двофазного матеріалу, де як друга фаза виступає ізоструктурний до нітриду титану високотемпературний нітрид молібдену γ-Mo₂N з кубічними гратками. Збільшення товщини шарів від 2 до 20 нм підвищує термічну стабільність механічних властивостей таких покриттів до високотемпературного (800 °С) відпалу. Для всього інтервалу товщини шарів 2 ÷ 20 нм високотемпературні відпали не призводять до зміни фазового складу покриттів, залишаючи нітрид молібдену в метастабільному γ-Mo₂N станіз кубічними решітками. Причиною стимулювання при осадженні і стабілізації при відпалі γ-Mo₂N стану є вплив другої складової багатошарової системи – нітрид титану (TіN) який має високу енергію зв’язку між металевими й азотними атомами і відповідний γ-Mo₂N тип кристалічних граток. Experiments have been made to investigate the influence of layer thickness and production conditions on the phase composition, structure and mechanical characteristics (hardness and modulus of elasticity) of vacuum-arc multilayer nanostructural coatings TiN-Mo₂N. It is shown that at a small layer thickness (≈2 nm) an epitaxial growth of isostructural cubic modifications of titanium nitride and molybdenum nitride is possible without two-phase state formation. At a greater thickness, a two-phase material is formed, where the second phase is presented by high-temperature cubic-lattice molybdenum nitride γ-Mo₂N, which is isostructural with respect to titanium nitride. A growth in layer thickness from 2 up to 20 nm increases the thermal stability of mechanical properties of these coatings at high-temperature. Experiments have been made to investigate the influence of layer thickness and production conditions on the phase composition, structure and mechanical characteristics (hardness and modulus of elasticity) of vacuum-arc multilayer nanostructural coatings TiN-Mo₂N. It is shown that at a small layer thickness (≈2 nm) an epitaxial growth of isostructural cubic modifications of titanium nitride and molybdenum nitride is possible without two-phase state formation. At a greater thickness, a two-phase material is formed, where the second phase is presented by high-temperature cubic-lattice molybdenum nitride γ-Mo₂N, which is isostructural with respect to titanium nitride. A growth in layer thickness from 2 up to 20 nm increases the thermal stability of mechanical properties of these coatings at high-temperature. annealings (800 °C). For the whole 2 ÷ 20 nm range of layer thicknesses, high-temperature annealings do not cause changes in the phase composition of coatings, leaving molybdenum nitride in the metastable γ-Mo₂N state with a cubic lattice. The reason for γ-Mo₂N state stimulation at deposition and γ-Mo₂N stabilization at annealing lies in the influence of the second constituent of the multilayer system, viz., titanium nitride (TiN), which has a high binding energy between metal and nitrogen atoms, and also, has the type of the crystal lattice corresponding to γ-Mo₂N